2003
DOI: 10.1074/jbc.m302830200
|View full text |Cite
|
Sign up to set email alerts
|

Estrogens Down-regulate p27 in Breast Cancer Cells through Skp2 and through Nuclear Export Mediated by the ERK Pathway

Abstract: The cyclin-dependent kinase (CDK) inhibitor p27Kip1 plays a key role in growth and development of the mammary epithelium and in breast cancer. p27Kip1 levels are regulated through ubiquitin/proteasome-mediated proteolysis, promoted by CDK2 and the F box protein Skp2 at the G 1 /S transition, and independent of Skp2 in mid-G 1 . We investigated the respective roles of Skp2 and subcellular localization of p27Kip1 in down-regulation of p27Kip1 induced in MCF-7 cells by estrogens. 17␤-Estradiol treatment increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
80
2

Year Published

2004
2004
2008
2008

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(89 citation statements)
references
References 82 publications
6
80
2
Order By: Relevance
“…Recent work indicates that induction of cell growth by E 2 in MCF7 cells may require activity of the PI-3K pathway (Lobenhofer et al, 2000) and the Ras/ERK pathway (Castoria et al, 2001). Furthermore, we reported that G1/S phase transition and Cdk2 activation induced by estrogens is inhibited by dominantnegative (DN) Ras mutants Foster, 2003;Zhu et al, 2003), and the MEK1 inhibitor PD98059 abrogated the increase in cyclin D1 accumulation resulting from estrogen treatment .…”
Section: Inhibition Of Apoptosis In Mcf7mentioning
confidence: 52%
See 4 more Smart Citations
“…Recent work indicates that induction of cell growth by E 2 in MCF7 cells may require activity of the PI-3K pathway (Lobenhofer et al, 2000) and the Ras/ERK pathway (Castoria et al, 2001). Furthermore, we reported that G1/S phase transition and Cdk2 activation induced by estrogens is inhibited by dominantnegative (DN) Ras mutants Foster, 2003;Zhu et al, 2003), and the MEK1 inhibitor PD98059 abrogated the increase in cyclin D1 accumulation resulting from estrogen treatment .…”
Section: Inhibition Of Apoptosis In Mcf7mentioning
confidence: 52%
“…The prolonged activation of ERK ( Figure 7A) in contrast to transient activation reported by others (Migliaccio et al, 1996) may be important to maintain the phosphorylation and inactivation of BAD, acting in concert with Akt. Prolonged ERK activation is also required for G1/S transition via enhanced cyclin D1 synthesis (Murphy et al, 2002) and p27 kip1 degradation (Foster, 2003). Together, the data in Figure 5 implicates a critical role for Ras/Raf/ERK in E 2 -promoted MCF7 cell survival.…”
Section: Estradiol Signals Through Two Pathways In Its Antiapoptotic mentioning
confidence: 68%
See 3 more Smart Citations